Unraveling the intricacies of circadian rhythm dynamics and their impact on mood fluctuations in human physiology: Clocked emotions: linking time to mood (Dhaka University Journal of Biological Sciences, 2026)
This study examines the moderating effect of gender on the link between mood swings and preferences for circadian rhythms. Cross-sectional recruitment was used to find 224 participants (108 males and 116 women), and the sample size had 95% statistical power to identify a small-to-medium effect. Mood states and circadian preferences were measured using the Brunel Mood Scale (BRUMS) and the Reduced Morningness-Eveningness Questionnaire (rMEQ), respectively. Statistical analyses, including Pearson correlation and multiple regression, revealed a little but substantial positive correlation (p < 0.05) between morning-oriented chronotypes and better mood outcomes. Furthermore, a two-way ANOVA showed that gender significantly influenced the link between mood changes and circadian type, with females exhibiting bigger mood variations. Participants who favor the mornings report better mood ratings, whereas those who prefer the nights report lower mood levels. These findings show a correlation between emotional well-being and circadian alignment, but further long-term research is needed to prove causation and look at other factors.Dhaka Univ. J. Biol. Sci. 35(1): 119-128, 2026 (January)